The influence of China, Russia and India on the future of democracy in the Euro-Asian region - Jörn Grävingholt; Julia Bader; Jörg Faust; Antje Kästner (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Many a democratisation process since the end of the Cold War has proved to be a flash in the pan. On a global scale the steps taken in democratisation have been backwards rather than forwards for some years, at least until recent events in the Arab world. Stable democracies have emerged mainly in the regional environment of other democracies, especially the European Union. Can, conversely, the growing strength of authoritarian models of governance in other world regions be attributed to the negative influence of undemocratic regional powers? Do countries such as China and Russia promote authoritarian rule in their regional environment? And what influence, on the other hand, do such rising democratic powers as India, Brazil and South Africa have? An analysis of the three major regional powers China,Russia and India in the context of neighbouring political regimes reveals a disturbing pattern: Russia has increasingly supported the governments of its authoritarian neighbours since the late 1990s. Since Georgia's Rose Revolution in 2003 it has also undermined and destabilised democratising regimes in its environment, as long as it can expect political benefit in the short term. China is clearly banking on regime stability in neighbouring countries and so, given the low level of democracy in the region, helping to maintain autocratic rule. It even protects such repressive dictatorships as Burma and North Korea against international interference. India, in contrast, hardly acts as a democratic counterbalance. After a largely unsuccessful period of actively interfering in South Asia, it has pursued a restrained foreign policy and so eased the tension of its relationship with such neighbours as Pakistan and China and increased its credibility as a representative of the concerns of the global “South” – without, however, making a significant contribution to greater democracy in its regional neighbourhood. It is true that the influence of regional powers on the regimes of neighbouring states should not be overestimated. Neither Russia nor China has yet created new dictatorships in its environment. The emergence of stable political systems also depends as much on long-term internal processes as on external influences. Yet the fact that authoritarian regional powers have problematical effects on their neighbours cannot be overlooked. Russia and China have at least helped to make successful democratic changes in their regions more difficult.
Keywords: 330